The effects of dexmedetomidine on postoperative tumor recurrence and patient survival after breast cancer surgery: a feasibility study - Luo, Jiamei; Xuan, Wei; Sun, Jiaxin; Wang, Xiaoqiang; Shi, Yumiao; Zhang, Yiqi; Yin, Wenjin; Shu, Huigang; Lu, Jinsong; Tian, Jie (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
Purpose Dexmedetomidine (Dexmed) is a highly selective alpha 2 adrenoceptor (α 2 -AR) agonist with excellent sedation and analgesic effects and is frequently used in breast cancer surgery. However, the exact impact of Dexmed on breast cancer prognosis is still unclear. The primary objective of this pilot study was to explore study feasibility (recruitment and dropout rates) for future large-scale randomized controlled trial (RCT) to test the hypothesis that intraoperative Dexmed reduced recurrence-free survival (RFS) and overall survival (OS) in patients after breast cancer surgery. Methods Interviews with patients were performed during the anesthetic preoperative visit for informed consent. Adult females scheduled for a mastectomy due to primary breast cancer were 1:1 randomised to saline (Group Control) or Dexmed (Group Dexmed) treatment groups. The primary outcomes were descriptions of study feasibility (recruitment and dropout rates). We also performed a preliminary analysis of RFS (time from surgery to the earliest date of recurrence/metastasis) and OS (time from surgery to the date of all-cause death) and collected data on percentages/numbers of circulating immune cells at pre- and 24 h post-operation. Results A total of 964 patients were screened; 40% (385/964) met the inclusion criteria, among which 39% (150/385) were enrolled and randomly assigned to either Group Control ( n = 75) or Group Dexmed ( n = 75). The median follow-up duration was 49 months (interquartile range (IQR): 34–58 months) for Group Control and 48 months (IQR: 33–60 months) for Group Dexmed. Five percent (5%, 8/150) patients were lost to follow-up and 1% (2/150) died. There was no significant difference in RFS and OS. The percentage/number of natural killer (NK), B and T-cell subsets and the CD4 + /CD8 + ratio were similar between groups at 24 h post-operation. Conclusion The pilot study was feasible to deliver. In a future definitive trial, the lower recruitment rate may be improved by increasing the number of anesthesiologists involved in the study. The study about the effects of Dexmed on long-term prognoses of breast cancer patients that is planned to follow this pilot study is a large-scaled randomized control study with the aim of providing evidence-based guidelines for rational use of Dexmed in patients undergoing breast cancer surgery. Trial registration Registered at ClinicalTrials.gov on October 20, 2016 (ID: NCT03109990). Graphical Abstract